PENGARUH BEBAN KERJA TERHADAP SEMANGAT KERJA PEGAWAI PADA DINAS PERTANIAN DAN PERKEBUNAN KABUPATEN BIMA - Rosdianti Rosdianti; Jaenab Jaenab; Ikbal Irawan (Jurnal Ilmiah Manajemen dan Akuntansi, 2024)
This research aims to determine the significant influence of workload on employee morale at the Bima Regency Agriculture and Plantation Service. This research is included in the Associative research category. The population in this research used all employees at the Bima Regency Agriculture and Plantation Service, totaling 222 employees. The research technique used was purposive sampling. The research sample used was all 44 employees in the extension sector.  The instrument in this research is a questionnaire with a Likert scale. Observation data collection techniques, questionnaires, literature study. The data analysis technique uses validity tests, reliability tests and simple linear regression tests and then processed using SPSS. The results of the research show that workload has a significant effect on employee morale at the Bima Regency Agriculture and Plantation Service.